2022
DOI: 10.20289/zfdergi.1096687
|View full text |Cite
|
Sign up to set email alerts
|

Kanatlı hayvanların beslenmesinde sürdürülebilirlik stratejileri

Abstract: Hayvansal üretimde sürdürülebilirlik; gelecek nesillerin gıda ihtiyaçlarını karşılama yeteneğinden ödün vermeden toplumun mevcut gıda ihtiyaçlarının karşılanması şeklinde tanımlanır. Kanatlı üretimi, hayvansal üretimin diğer alanlarına kıyasla daha çevre dostu olmasına rağmen sera gazları, ötrofikasyon ve asidifikasyon gibi çevresel etkileri göz ardı edilmemelidir. Kanatlı üretim zincirinde, yem üretimi ve nakliye küresel ısınma potansiyalinin %70’ini oluştururken, gübre yönetimi ise ötrofikasyon ve asidifikas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
1
0
1
Order By: Relevance
“…In spite of insignificant differences between treatments in egg weight that had a big influence on chick's quality especially on chick's length, there were a significant difference in Beak to Toe Length toward all groups subjected to change in temperature during incubating period (table 3), the same trend happened in toe length of chicks, whereas, the were no significant differences in the rest of chick's quality. [60] revealed that changing in temperature during incubation period did not affect chick's weight, also, [61] found there was no significant differences in chick weight, length and quality score between treatments. 2 Different letters in columns indicate significant differences between treatments.…”
Section: External Chick's Qualitymentioning
confidence: 88%
“…In spite of insignificant differences between treatments in egg weight that had a big influence on chick's quality especially on chick's length, there were a significant difference in Beak to Toe Length toward all groups subjected to change in temperature during incubating period (table 3), the same trend happened in toe length of chicks, whereas, the were no significant differences in the rest of chick's quality. [60] revealed that changing in temperature during incubation period did not affect chick's weight, also, [61] found there was no significant differences in chick weight, length and quality score between treatments. 2 Different letters in columns indicate significant differences between treatments.…”
Section: External Chick's Qualitymentioning
confidence: 88%
“…Öte yandan, sürdürülebilir hayvansal üretim için çevre ayak izini azaltacak besleme stratejilerinde geliştirilmesi gereklidir (Kırkpınar & Atan, 2022). Modern hayvancılık, rasyon hazırlanırken hayvanların besin madde ihtiyaçlarını karşılamak ve ekonomik bir karma yem oluşturma amacı ile sınırlı kalmayıp, aynı zamanda çevre ayak izini de korumaya yönelmiştir (Mackenzie et al, 2016;Garcia-Launay et al, 2018;Meriç & Koç, 2021).…”
Section: Introductionunclassified